The Role of the National Land Agency of Banten Provoince in Erradiating Land Mafiah (Case Study of Banten Provincial BPN Regional Office) - Muhammad Nasir (Journal of Law, Politic and Humanities, 2024)
Law Number 5 of 1960 concerning Basic Agrarian Principles (UUPA) provides a clear legal framework regarding land ownership, including registration and certification procedures. This UUPA is expected to protect the rights of land owners from land mafia practices. However, in practice, the implementation of the UUPA has not been optimal and there are still legal loopholes that are exploited by land mafia actors. Land mafia is a land crime committed by a group of people to illegally control land belonging to other people. Land mafia perpetrators use methods that violate the law in a planned, neat and systematic manner. To take action against land mafia perpetrators, several criminal offenses can be used, including:Article 167 of the Criminal Code concerning unlawful entry into a house or yard Article 263 of the Criminal Code concerning making a fake document which can give rise to a right to land is an operandi of the Land Mafia and social inequality that can be seen from around us, especially in rural areas, where there are many land owners and land owners. capital is very inversely proportional. That is the aim of the UUPA to prevent the monopoly of capital owners on land owners.